2011
DOI: 10.1038/emboj.2011.379
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial contact site complex, a determinant of mitochondrial architecture

Abstract: Mitochondria are organelles with a complex architecture. They are bounded by an envelope consisting of the outer membrane and the inner boundary membrane (IBM). Narrow crista junctions (CJs) link the IBM to the cristae. OMs and IBMs are firmly connected by contact sites (CS). The molecular nature of the CS remained unknown. Using quantitative high-resolution mass spectrometry we identified a novel complex, the mitochondrial contact site (MICOS) complex, formed by a set of mitochondrial membrane proteins that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

49
579
1
24

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 418 publications
(653 citation statements)
references
References 63 publications
49
579
1
24
Order By: Relevance
“…Recently, several groups identified a large protein complex, MICOS complex (mitochondrial contact site and cristae organizing system; previously named MINOS, MitOS, Mitofilin or Fcj1 complex ), that has a crucial role in the formation of cristae junctions, contact sites to the outer membrane, and the organization of inner membrane. [10][11][12][13][14] In yeast, MICOS consists of at least six subunits: Mic60 (Fcj1), Mic10 (Mio10/Mcs10/Mos1), Mic19 (Aim13/Mcs19), Mic26 (Mio27/Mcs29/Mos2), Mic12 (Aim5/ Msc12) and Mic27 (Aim37/Mcs27). In mammals, five subunits of MICOS have already been identified, including Mic60 (Mitofilin/IMMT), Mic10 (MINOS1), Mic19 (CHCHD3/MINOS3), Mic25 (CHCHD6/CHCM1) and Mic27 (APOOL).…”
mentioning
confidence: 99%
“…Recently, several groups identified a large protein complex, MICOS complex (mitochondrial contact site and cristae organizing system; previously named MINOS, MitOS, Mitofilin or Fcj1 complex ), that has a crucial role in the formation of cristae junctions, contact sites to the outer membrane, and the organization of inner membrane. [10][11][12][13][14] In yeast, MICOS consists of at least six subunits: Mic60 (Fcj1), Mic10 (Mio10/Mcs10/Mos1), Mic19 (Aim13/Mcs19), Mic26 (Mio27/Mcs29/Mos2), Mic12 (Aim5/ Msc12) and Mic27 (Aim37/Mcs27). In mammals, five subunits of MICOS have already been identified, including Mic60 (Mitofilin/IMMT), Mic10 (MINOS1), Mic19 (CHCHD3/MINOS3), Mic25 (CHCHD6/CHCM1) and Mic27 (APOOL).…”
mentioning
confidence: 99%
“…In human cells, mitofilin was found to interact with the sorting and assembly machinery of the outer membrane (SAM complex) that has a central role in the biogenesis of outer membrane proteins ( Figure 2B) (Xie et al , 2007 ;Darshi et al , 2011 ;Alkhaja et al , 2012 ;Ott et al , 2012 ). In yeast, interactions of mitofilincontaining protein complexes of the inner membrane with the SAM complex, the TOM complex, porin channels and Ugo1 have been reported (Figure 2A) (Harner et al , 2011 ;Hoppins et al , 2011 ;von der Malsburg et al , 2011 ;K ö rner et al, 2012 ;Zerbes et al , 2012 ). The interaction of mitofilin with the TOM complex was shown to support the import of precursor proteins into the intermembrane space via the mitochondrial intermembrane space assembly (MIA) machinery (von der Malsburg et al , 2011 ).…”
Section: Structural and Functional Links Of Crista Junctions And Membmentioning
confidence: 99%
“…These findings have prompted the hypothesis of a structural and functional connection between contact sites and crista junctions. The possibility of such an overlapping localization has been repeatedly addressed, although never comprehensively clarified (van der Klei et al , 1994 ;Perkins et al , 1997 ;Reichert and Neupert , 2002 ;Harner et al , 2011 ;K ö rner et al, 2012 ). Some studies have suggested that the integrity of crista junctions may depend on their anchoring to the outer mitochondrial membrane via mitofilin-containing contact sites (Harner et al , 2011 ;K ö rner et al, 2012 ;Ott et al , 2012 ).…”
Section: Structural and Functional Links Of Crista Junctions And Membmentioning
confidence: 99%
See 2 more Smart Citations